Peningkatan Kemampuan Menyunting Karangan dengan Menerapkan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Pada Siswa Kelas IX.6 di SMP Negeri 13 Pekanbaru - Mimi Rosita (Instructional Development Journal, 2018)
This research is a classroom action research with three cycles carried out on class IX.6 students in Pekanbaru Public Middle 13. Cycle I, cycle II, and cycle III consisted of planning, action, observation, and reflection. The subject of this study, namely the ability to edit essays in class IX.6 students in Pekanbaru Public Middle 13. The variables in this study were the ability to edit essays and cooperative learning types think-pair-share (TPS). The results of this study indicate that after following essay editing learning by applying the cooperative learning model think-pair-share (TPS) type, the average grade of class IX.6 students in SMP Negeri 13 Pekanbaru from cycle I to cycle III has increased. The ability to edit essays of class IX.6 students of SMP Negeri 13 Pekanbaru after participating in learning by applying the cooperative learning model of the think-pair-share type has increased. The results of the first cycle data analysis up to the third cycle continued to increase. The test results in the first cycle class average of 69.37, in the second cycle of 74, and in the third cycle of 83. This shows an increase from the first cycle to the second cycle of 5.03 and has increased again from cycle II to cycle III of 9. The acquisition of this result shows that editing learning essays with the application of the cooperative learning model think-pair-share type can be said to be successful. Based on the results of these studies, it can be concluded that the ability to edit essays by class IX.6 students in Pekanbaru State Junior High School 13 has increased after attending learning with the think-pair-share (TPS) cooperative learning model. The suggestions in this study are (1) Indonesian language and literature teachers in the learning process should apply the cooperative pair type think-share (TPS) learning model as an alternative to essay editing learning; (2) more students practice editing essays; and (3) researchers in the field of education and language should always be motivated to carry out research on the application of other learning models so that new alternative learning techniques are obtained, especially about writing learning such as editing essays.